Intrusion-Tolerant Broadcast and Agreement Abstractions in the Presence of Byzantine Processes - Mostefaoui, Achour; Raynal, Michel (IEEE transactions on parallel and distributed systems, 2016)
A process commits a Byzantine failure when its behavior does not comply with the algorithm it is assumed to execute. Considering asynchronous message-passing systems, this paper presents distributed abstractions, and associated algorithms, that allow non-faulty processes to correctly cooperate, despite the uncertainty created by the net effect of asynchrony and Byzantine failures. These abstractions are broadcast abstractions (namely, no-duplicity broadcast, reliable broadcast, and validated broadcast), and agreement abstraction (namely, consensus). While no-duplicity broadcast and reliable broadcast are well-known one-to-all communication abstractions, validated broadcast is a new all-to-all communication abstraction designed to address agreement problems. After having introduced these abstractions, the paper presents an algorithm implementing validated broadcast on top of reliable broadcast. Then the paper presents two consensus algorithms, which are reductions of multivalued consensus to binary consensus. The first one is a generic algorithm, that can be instantiated with unreliable broadcast or no-duplicity broadcast, while the second is a consensus algorithm based on validated broadcast. Finally, a third algorithm is presented that solves the binary consensus problem. This algorithm is a randomized algorithm based on validated broadcast and a common coin. The presentation of all the abstractions and their algorithms is done incrementally.